EDUKASI DAN PELATIHAN PEMANFAATAN SERAI DAN DAUN JERUK SEBAGAI PRODUK PENCEGAHAN DEMAM BERDARAH DI DESA GEDONG, NGADIROJO, WONOGIRI - Crescentiana Emy Dhurhania; Atur Semartini; Rista Ariyani; Rixka Yulianti; Yuli Yuli; Candra Wulandari (Stikes Syedza Saintika Padang, 2022)
Dengue Hemorrhagic Fever is one of the disease cases that has the highest prevalence in Central Java. One of the causes are the lack of knowledge of the dangers of DHF and how to prevent it. This community service program is carried out as a preventive effort of dengue fever by utilizing nutritious herbal plants around the area. Community service was conducted in Gedong, Ngadirojo, Wonogiri which was began by counselling on dengue fever and the use of lemongrass and kaffir lime leaves, then was continued with the manufacture of repellent spray products from these plants. The evaluation of the community service program was carried out with a pretest and posttest to determine the level of community knowledge before and after the program. The average value of the pretest was 60.96 and the posttest obtained an average value of 80.44 which indicated that there was an increase in community knowledge before and after the extension activities were carried out.